Prevalence of Malaria Parasite Among Students of Federal University Wukari, Taraba State, Nigeria - Twan, M. S.; Ronald, A. W. (African Journal of Sciences and Traditional Medicine, 2024)
This study examined the prevalence of malaria parasite among students of Federal University Wukari, Taraba state, Nigeria. This study adopted experimental (survey) design, Primary data was obtained from the Students of Federal University Wukari to access the prevalence of Malaria infection, and the sample size calculated approximately to be 400 as the baseline sample size of our study to avoid bias in the selection of the tertiary students. Chi-square test was used to determine the mean differences in prevalence between age groups and gender at 95% confidence level using Statistical Package of Social Sciences at P-values less than 0.05 were considered as significant. The findings of the study revealed that the prevalence of malaria infection among the students examined was 57.0%, P. falciparum (57.90%) is more incident species infecting the student, it is also indicated that the males have a higher prevalence rate (57.0%) than their female counterparts (43.0%) and the difference in age do not vary significantly in the infection of malaria rather the prevalence is a function of exposure rather than age. Therefore, the enforcement of the rule on frequent public sanitation within the university hostels by the university management is essential and recommended, and he university management should periodically educate students on the need to use a mosquito bed net, fumigation, and indoor residual spray in their surroundings among other recommendations.